Design, synthesis and in vitro biological evaluation of marine phidianidine derivatives as potential anti-inflammatory agents. (1st October 2022) - Xu, Quan; Zhao, Ning; Liu, Jin; Song, Jin-Qian; Huang, Li-Hua; Wang, Hong; Li, Xu-Wen; Pang, Tao; Guo, Yue-Wei
Graphical abstract: Highlights: A series of phidianidine derivatives were synthesized to study anti-inflammatory activity. Compounds 9a and 22c exhibited excellent anti-inflammatory activity and low toxicity on IL-17A production in PMA and ionomycin-stimulated EL4 cells. Compound 9a could decrease the STAT3 phosphorylation at Y705 to inhibit IL-17A production in EL-4 cells. Molecular docking analysis explained our SAR study. Abstract: Phidianidines A and B are novel marine indole alkaloids with various biological activities. Based on their potential anti-inflammatory properties, a series of phidianidine derivatives were designed, synthesized, and tested for their effects on IL-17A production in PMA/ionomycin-stimulated T -cell-lymphoma EL-4 cells. Compounds 9a and 22c exhibited excellent anti-inflammatory activity and low toxicity, with IC50 values of 7.7 μM and 5.3 μM for IL-17A production in PMA/ionomycin-stimulated EL-4 cells, respectively. Further mechanistic study showed that 9a could decrease the STAT3 phosphorylation at Y705 to inhibit IL-17A production in EL-4 cells, indicating its ability of preventing the differentiation of Th17 cells and their possible function. This research may give an insight for the discovery of marine indole alkaloid derived anti-inflammatory drug leads for the treatment of T cell-mediated diseases.